Digital Literacy Movement Enhances Personal Skills And Learning Habits In Elementary School Students: Gerakan Literasi Digital Menumbuhkan Keterampilan pribadi dan Kebiasaan Belajar Siswa Sekolah Dasar - Nuryanti; Fahyuni, Eni Fariyatul (Indonesian Journal of Innovation Studies, 2026)
General Background: Digital skills are increasingly required for teachers to create interactive, creative, and joyful learning. Specific Background: At SDN Kenongo 1, digital technology has been integrated into classroom learning, although differences in teachers’ digital competence and available resources remain. Knowledge Gap: Uneven digital skills, unstable internet access, limited devices, and preparation time create challenges in consistent digital learning implementation. Aims: This study analyzes teachers’ professional competence in digital skills for Joyful learning and identifies classroom implementation barriers. Results: Using a qualitative phenomenological approach, the study found that 100% of teachers prepared learning modules aligned with teaching materials, while 75% implemented learning according to their modules. Novelty: The study highlights the combination of digital competence, school support, varied digital media, and active student participation in Joyful learning. Implications: Structured training and continuous learning-community mentoring are recommended to support more equitable digital competence development in elementary schools. Key Findings Highlights A total of 20 educators demonstrated varying levels of technological proficiency, ranging from high to low. Activities such as games, exploration, interactive media, and group work made the students more active, enthusiastic, and confident. The availability of Wi-Fi, LCD screens, projectors, training, and learning communities supports the learning process, but network connectivity, devices, and preparation time remain challenges. Keywords: Digital Skills, Joyful Learning, Teacher Professional Competence, Digital Learning, Elementary Education